2016
DOI: 10.3390/ijms17091406
|View full text |Cite
|
Sign up to set email alerts
|

Saponin-Based Nanoemulsification Improves the Antioxidant Properties of Vitamin A and E in AML-12 Cells

Abstract: Our work aimed to investigate the protective effects of saponin-based nanoemulsions of vitamin A and E against oxidative stress-induced cellular damage in AML-12 cells. Saponin nanoemulsions of vitamin A (SAN) and vitamin E (SEN) were prepared by high-pressure homogenization and characterized in terms of size, zeta potential, and polydispersity index. SEN and SAN protect AML-12 cells against oxidative stress-induced cellular damage more efficiently via scavenging reactive oxygen species (ROS), and reducing DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Liposomes for parenteral administration can also ameliorate the stability of verbascoside by preventing its hydrolysis [ 9 ]. Nevertheless, nanoemulsions may increase the stability of natural compounds and encapsulation improves the antioxidant activity of APIs [ 19 ]. It is worth noting that our PL-SNEDDS compositions potentiated the free radical scavenging activity of P. lanceolata extract compared to positive control (non-encapsulated P. lanceolata extract).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomes for parenteral administration can also ameliorate the stability of verbascoside by preventing its hydrolysis [ 9 ]. Nevertheless, nanoemulsions may increase the stability of natural compounds and encapsulation improves the antioxidant activity of APIs [ 19 ]. It is worth noting that our PL-SNEDDS compositions potentiated the free radical scavenging activity of P. lanceolata extract compared to positive control (non-encapsulated P. lanceolata extract).…”
Section: Discussionmentioning
confidence: 99%
“…DPPH reduction assay was an efficient and rapid method to screen the scavenger activity of PL-SNEDDS samples in vitro [ 20 ]. DPPH reaction is predictive but not sufficient to certify the therapeutic potential of P. lanceolata extract [ 19 ]. Therefore, ear inflammation test was carried out.…”
Section: Discussionmentioning
confidence: 99%
“…The coarse emulsion was then processed two times in a ultra-high-pressure homogenizer at 200 MPa. The resulting nanoemulsions (droplet size < 300 nm) were used for preparation of retinyl acetate micelles for in vitro evaluation of their biological functions [ 89 ]. Tanglao et al (2019) also used whey proteins (polymerized) to encapsulate vitamin A in virgin coconut O/W emulsions.…”
Section: Encapsulation Of Lipid-soluble Bioactive Compounds By Nanmentioning
confidence: 99%
“…The authors demonstrated that vitamins were more effective to suppress lipid peroxidation, protein carbonylation, and DNA damage reactions in emulsified state compared to their non-emulsified form. In another recent study, nanoemulsions containing Tween 80 in combination with various encapsulating agents (Capsul, maltodextrin, sodium caseinate) were successfully used to encapsulate vitamins A and E for application in extruded feed products [ 89 ].…”
Section: Encapsulation Of Lipid-soluble Bioactive Compounds By Nanmentioning
confidence: 99%
“…Meanwhile, ROS may lead to a series of diseases, such as diabetes, hypertension, cancer and atherosclerotic cardiovascular disease (Finkel et al , 2000; Memarpoor-Yazdi et al , 2012 ). Recently, more and more researchers had focused on extraction of novel, safe and natural antioxidants, for instance, carotenoids and vitamin A ( Choudhry et al , 2016 ; Korekar et al , 2014; Maadane et al , 2015 ; Páramo et al , 2012). Such antioxidants are mainly obtained from vegetables, fruits, foods ( Geetha et al , 2002 ; Podsedk, 2007 ), and are regarded as the second antioxidant defense line in living organisms ( Yigit et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%